1999
DOI: 10.1080/014850199263002
|View full text |Cite
|
Sign up to set email alerts
|

Semen Culture, Leukocytospermia, and the Presence of Sperm Antibodies in Seminal Hyperviscosity

Abstract: Seminal hyperviscosity is generally thought to reveal genitourinary infection. The aim of the present work was to study this hypothesis. A total of 65 semen samples were obtained from males presenting for infertility screening. The samples were evaluated according to WHO criteria and microbiologically investigated, including culturing for Mycoplasma hominis and Ureaplasma urealyticum, and microscopic observation of Chlamydia trachomatis by a direct fluorescence assay. Determination of local antisperm antibodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 13 publications
(17 reference statements)
3
14
0
1
Order By: Relevance
“…Seminal antibodies to C. trachomatis are not associated with leucocyte count and leucocytospermia do not appear to have an effect either on spermatic function or the immune system response to sperm [16]. A lack of association between chlamydial antibodies in semen and leucocytospermia is consistent with the results of Munuce et al, who do not find differences in the seminal leucocyte concentration comparing two groups of men with and without C. trachomatis genital infection [23].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Seminal antibodies to C. trachomatis are not associated with leucocyte count and leucocytospermia do not appear to have an effect either on spermatic function or the immune system response to sperm [16]. A lack of association between chlamydial antibodies in semen and leucocytospermia is consistent with the results of Munuce et al, who do not find differences in the seminal leucocyte concentration comparing two groups of men with and without C. trachomatis genital infection [23].…”
Section: Discussionsupporting
confidence: 82%
“…In this and other studies [11,12,16] an association between the presence of antichlamydial IgA antibodies in ejaculate and some seminal variables such as sperm count and motility in semen was not found. These results suggest that IgA antibodies to C. trachomatis had no effect on sperm motility, since these antibodies are not associated with increased antispermatic antibodies levels, as described by Habermann/Krause [16] and Munuce et al [23].…”
Section: Discussionsupporting
confidence: 59%
“…Munuce et al [17] employed treatment with antibiotics in subjects with infections of the genital tract, with and without SHV. Therapy was based on the respective microorganism and antibiogram.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that there is a good deal of disagreement in this field. According to Munuce et al [17], there is no association between SHV and semen culture positivity, leukospermia or the presence of sperm antibodies. In addition, there is no correlation between SHV and human immunodeficiency virus infection [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, Bezold et al found no difference in prevalence of C. trachomatis and other pathogens between asymptomatic male infertile patients with and without leukocytospermia [82]. Also, other authors found no relation between infection with C. trachomatis and leukocyte count in semen [65,83,84].…”
Section: The Controversial Role Of Leukocytospermia On Fertilitymentioning
confidence: 95%